2013
DOI: 10.4103/0250-474x.119813
|View full text |Cite
|
Sign up to set email alerts
|

Mutual Amide Prodrug of Etodolac-glucosamine: Synthesis, Characterization and Pharmacological Screening

Abstract: Etodolac, a nonsteroidal antiinflammatory drug, widely used in arthritis is associated with gastric ulceration and irritation due to presence of free carboxylic group. The current investigation reports synthesis of mutual amide prodrug of etodolac by masking free carboxylic group with glucosamine, a nutritional supplement for treatment of arthritis. Confirmation and characterization of the structure of the synthesized prodrug done by elemental and spectroscopy analysis, melting point, determination of migratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 15 publications
0
8
1
Order By: Relevance
“…16 Previous research has demonstrated that the chemical conjugation of GlcN by amidation with etodolac can reduce the toxicity of etodolac. 17 Alternatively, esterification with Gly-Val can improve the intestinal permeation of GlcN itself. 18 Therefore, in the study presented here, the amino sugar GlcN, which is naturally transported by GLUT1, -2, and -4, 19 was used to conjugate target dipeptide PO.…”
Section: ■ Introductionmentioning
confidence: 99%
“…16 Previous research has demonstrated that the chemical conjugation of GlcN by amidation with etodolac can reduce the toxicity of etodolac. 17 Alternatively, esterification with Gly-Val can improve the intestinal permeation of GlcN itself. 18 Therefore, in the study presented here, the amino sugar GlcN, which is naturally transported by GLUT1, -2, and -4, 19 was used to conjugate target dipeptide PO.…”
Section: ■ Introductionmentioning
confidence: 99%
“…For general background to and the pharmacological activity of Schiff base compounds, see: Shapiro (1998); Villar et al (2004); Venugopal & Jayashree (2008); Pandey et al (2003); Bhat et al (2005); Wadher et al (2009). For related structures, see: Fun et al (2011a,b).…”
Section: Related Literaturementioning
confidence: 99%
“…(Shapiro, 1998). They have been found to posses the pharmacological activities such as antimalarial, anticancer (Villar et al, 2004) antibacterial (Venugopal & Jayashree, 2008) antifungal (Pandey et al, 2003) antitubercular (Bhat et al, 2005), anti-inflammatory and antimicrobial (Wadher et al, 2009) properties.…”
Section: Data Collectionmentioning
confidence: 99%
“…They have attracted particular interest due to their biological activities (Shapiro, 1998). They have been found to posses the pharmacological activities such as antimalarial, anticancer, antibacterial (Venugopal & Jayashree, 2008), antifungal (Pandey et al, 2003), antitubercular (Bhat et al, 2005), anti-inflammatoryand antimicrobial (Wadher et al, 2009) properties.…”
Section: S1 Commentmentioning
confidence: 99%